Is a Contemporary Hegelian Philosophy of Nature Possible? - Arredondo, Xavier Aranda (ETHICS IN PROGRESS, 2024)
Hegel’s philosophy of nature (Naturphilosophie) is impossible to separate from the rest of his system, in which nature is shown as a reflection of the idea (Idee) as presented in the logic (in the Enzyklopädie der philosophischen Wissenschaften). The system composed by logic, nature, and spirit, represents a dialectical relation in which logic as the universal, nature as the particular, and spirit as the singular, mediate through one another and develop as immanent and constitutive parts of the system as a whole. Yet, the goal of the philosophy of nature is not unrelated to a philosophy of science in the contemporary sense. The latter aims to solve (among other problems) the problem of dualism between the conceptual scheme/the world and the demarcation of science (and knowledge), where the crucial difference is that the Hegelian philosophy of nature benefits from having an answer to these in the form of the absolute idea (die absolute Idee). In a contemporary sense, the constitution of these problematics would follow an abductive reasoning where the Hegelian idea (Idee) would solve these crucial problems for philosophy of science. The following paper will attempt to provide some guiding points for such a project and suggest the assumptions necessary for its development, with the sole purpose of underscoring the similarities and differences between the Hegelian philosophy of nature and a contemporary philosophy of science.